A retrospective study of febrile seizures among children admitted in a tertiary care hospital - Potdar, Pralhad Sureshrao (International Journal Of Community Medicine And Public Health, 2018)
Background: Convulsion is the most common neurologic finding in children (10%). Prevention of febrile convulsions is therefore desirable, and is of particular relevance in children with factors carrying a high risk of recurrence. Aim and Objectives were to study the demographic profile and some risk factors of febrile seizures among children. Methods: A record based descriptive cross-sectional study was conducted at paediatric department of Dr. S.C.GMC, Nanded. Considering inclusion & exclusion criteria all children in the 6 month to 6 year age who were diagnosed as having febrile convulsion admitted during January to December 2015 were included in the study. Results: Of the 288 children 173 (60.1%) were boys and 115 (39.9%) were girls. 46.9% children were in the 1-3 year age group. Mean age of occurrence was 2.8 years (±1.5 years). In this study, 80.2% (231) of the patients had simple and 19.8% (57) had the complex form of febrile seizure. In our study, 51.73% (149) of affected children had positive family history of febrile seizure. URTI (9.7%) followed by AGE (7.3%) was the most common co-morbidity. 54.2% children were hospitalized for 1-3 days. Conclusions: Most of the children had a positive family history and the most common causative factor was URTI, LRTI, AGE etc. are associated with febrile convulsion and these diseases can be managed effectively thereby reducing the occurrence of febrile convulsion.